Cover Feature: Chemical Vapor Deposition for Advanced Polymer Electrolyte Fuel Cell Membranes (ChemElectroChem 8/2022). Issue 8 (15th March 2022) - Bellomo, Nicolas; Michel, Marc; Pistillo, Bianca Rita; White, Robin J.; Barborini, Emanuele; Lenoble, Damien
Abstract : The Cover Feature shows a generalised illustration of the dynamics of chemical vapour deposition for the preparation of proton exchange membranes. More information can be found in the Review by N. Bellomo et al .